Pengaruh Pelatihan Timbang Terima Pasien Terhadap Penerapan Keselamatan Pasien Oleh Perawat Pelaksana di RSUD Raden Mattaher Jambi - Dewi, Mursidah (JURNAL HEALTH AND SPORT, 2012)
The patient handover help nurses to identify the service area that require improvement to improve patient safety. The purpose of this research was to identify the effect of training on patient handover with an effective communication approach integrated to the implementation of patient safety to the implementation of handover and patient safety by nurse practitioner at RSUD Raden Mattaher Jambi. This research used preexperimental design, with one group pretest posttest design. The sample is 43 nurse practitioner. From the data analysis, it has been recognized that there is a significant improvement in the implementation of patient handover and patient safety after getting a training and guidance on patient handover (p value : 0.000). The conclusion, there is an effect of training on patient handover to the implementation of handover and patient safety. Hospital should implements patient handover effectively in the form of policies, direction and evaluation to continuity of nursing care that have an impact on improving the implementation of patient safety.